2023
DOI: 10.3389/fpos.2022.1063741
|View full text |Cite
|
Sign up to set email alerts
|

Complex dynamics of climate emotions among environmentally active Finnish and American young people

Abstract: Climate emotions have become an increasingly salient issue since the beginning of the 2000s. This paper draws on data from in-depth interviews from the United States (USA) and Finland to provide insight into the complex dynamics of climate emotions in 23 environmentally active young people in these two countries. The analysis centers on two main themes: (a) complex dynamics of climate emotions and (b) identities and felt social expectations. The results support recent research about the importance of anger, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Furthermore, the authors did not rigorously ask every question to every participant, but considerable space was given to explore the emerging new themes regarding emotions towards the climate. The findings showed an association with climate emotions in young Americans: their emotions about climate change, such as anger, pain, and guilt, were very common [4]. Gunasiri et al (2022) showed the positive impacts of the climate on feeling optimistic in quantitative and qualitative studies.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, the authors did not rigorously ask every question to every participant, but considerable space was given to explore the emerging new themes regarding emotions towards the climate. The findings showed an association with climate emotions in young Americans: their emotions about climate change, such as anger, pain, and guilt, were very common [4]. Gunasiri et al (2022) showed the positive impacts of the climate on feeling optimistic in quantitative and qualitative studies.…”
Section: Resultsmentioning
confidence: 86%
“…-Residence: Alpine region -Sex: male [4] This study examined the factors associated with climate emotions in young Americans.…”
Section: One Case Description Of a Mountaineer In Central Europementioning
confidence: 99%
See 1 more Smart Citation
“…If a participant used these words, however, the interviewer mirrored their language and understanding of the emotions. Second, the interview topic can be challenging when participants find it difficult and uncomfortable to reflect upon and speak about such emotions (Coppola and Pihkala, 2023). With this in mind, it was important for the interviewer to navigate, and sometimes avoid, blatant feelings and expressions of guilt or shame.…”
Section: Interview Guidementioning
confidence: 99%
“…Kasvatustieteellistä ja yhteiskunnallista keskustelua 2020-luvulla raamittaa enenevissä määrin huoli ympäristön heikentyvästä tilasta, kiihtyvästä ilmastonmuutoksesta ja koko ihmiskunnan sosiokulttuurisesta hyvinvoinnista (ks. Värri 2018;Pulkki 2021;Joutsenvirta & Salonen 2020;Salonen & Bardy 2015;Coppola & Pihkala 2023). Kasvatustiede ei ole oppia ympäristöstä, mutta silloin kun puhutaan ihmisen tarpeesta muuntautua selviämään uudenlaisessa maailmassa, joka on biodiversiteetiltään köyhempi ja luonnonresursseiltaan huvennut, ollaan kasvatustieteen ydinalueilla.…”
Section: Johdantounclassified